ULCERATIVE COLITIS AND CROHN DISEASE IN CHILDREN - AN EVOLVING PROBLEM IN ROMANIA - Cristina Becheanu; Gabriela Lesanu; Roxana Smadeanu; Iulia Tincu (Amaltea Medical Publishing House, 2014)
Objectives. In the past few years we observed an increase in the number of patients with infl ammatory bowel disease. We aimed to determine the epidemiology of this pathology among children in Romania over a 10 years period. Matherial and methods. The survey was conducted in Pediatric Gastroenterology Departments in Bucharest. We selected patients beeing carred for infl ammatory bowel disease in 2011. A similar study, performed 10 years ago in 2001, reported the same epidemiologic characteristics and comparative data were available. Results. In 2001 we report 74 cases of infl ammatory bowel disease, while there were 21 cases mentioned in 2001. We identifi ed 35 cases of Crohn disease (47.29%) and 39 patients with ulcerative colitis (52.7%). The previous study reported 17 (81%) and 4 (19%), respectively. The mean age of onset of symptoms is 10.2 while in 2001 this was 13.2 years. Conclusions. Infl ammatory bowel disease has tripled in the last 10 years. Ulcerative colitis is still the most frequent form but we report a growing number of cases with Crohn disease.